Effect of home environment on neuropsychiatric development in preterm infants discharged from NICU at 18 months corrected age - Yuan Tian; Chuncao Zhang; Li Shen; Haifeng Jiang; Feng Liu; Jinjin Chen; Xia Hong (General Psychiatry)
Background There have been numerous intervention studies focusing on the development of preterm infants, but there has been limited investigation into the home environment as a determinant of developmental outcomes in preterm infants. The aspects and extent to which the home environment affects the early (18 months corrected age) neuropsychological development of preterm infants are still unclear.Aims This study aimed to analyse the effect of the home environment on the neuropsychiatric development of preterm infants at 18 months corrected age after discharge from the neonatal intensive care unit (NICU). It also sought to provide a basis for promoting neuropsychiatric development among preterm infants by improving the home environment.Methods In this retrospective cross-sectional study, 275 preterm infants born between January 2019 and January 2022 were followed up for systematic management after discharge from the NICU at Shanghai Children’s Hospital. The Home Nurture Environment Questionnaire was used to assess the home environment of the infants and analyse its impact on the developmental quotient (evaluated by the Gesell Developmental Scale) and the rate of developmental delays at 18 months corrected age.Results A total of 41.454% of the infants were extremely preterm. The developmental quotient scores at 18 months corrected age were in the middle of the scale. The language domain had the highest rate of developmental delay (46.182%), followed by the adaptive domain (37.091%). Multiple logistic regression analyses showed that compared with infants in supportive home environments, infants with moderate/unsupportive home environments had significantly elevated risks of development delay: 2.162-fold for global (odds ratio (OR) 2.162, 95% confidence interval (CI) 1.274 to 3.665, p=0.004), 2.193-fold for fine motor (OR 2.193, 95% CI 1.161 to 4.140, p=0.016), 2.249-fold for language (OR 2.249, 95% CI 1.336 to 3.786, p=0.002) and 2.042-fold for personal-social (OR 2.042, 95% CI 1.149 to 3.628, p=0.015).Conclusions A supportive home environment is a crucial protective factor for the neuropsychological development of preterm infants. It is associated with higher developmental quotient scores and protects against neuropsychiatric delays. Incorporating evaluation and continuous improvement of the home environment into the management framework for preterm infants to promote optimal neurodevelopment is essential.